Immune profiles in mouse brain and testes infected by Zika virus with variable pathogenicity - Shang, Jingzhe; Li, Chunfeng; Jin, Zhujia; Zu, Shulong; Chen, Songjie; Chen, Junlan; Chen, Ziyi; Tang, Hua; Qin, Cheng-Feng; Ye, Qing; Wu, Aiping (Frontiers in Cellular and Infection Microbiology, 2022)
The Zika virus is responsible for neurological diseases such as microcephaly, Guillain-Barré syndrome, neuropathy, and myelitis in human adults and children. Previous studies have shown that the Zika virus can infect nerve progenitor cells and interfere with neural development. However, it is unclear how the immune system responds to infection with Zika viruses with variable pathogenicity. Here, we used two Zika strains with relatively different pathogenicity, the Asian ancestral strain CAM/2010 and the America pandemic strain GZ01/2016, to infect the brains of mice. We found that both strains elicited a strong immune response. Notably, the strain with relatively high pathogenicity, GZ01/2016, caused more intense immune regulation, with stronger CD8+ T cell and macrophage activation at 14 days post infection (dpi), as well as a greater immune gene disturbance. Notably, several TNF family genes were upregulated at 14 dpi, including Tnfrsf9, Tnfsf13, Tnfrsf8, Cd40, and Tnfsf10. It was notable that GZ01/2016 could maintain the survival of nerve cells at 7dpi but caused neurological disorders at 14dpi. These results indicate that Zika viruses with high pathogenicity may induce sustained activation of the immune system leading to nerve tissue damage.